2013
DOI: 10.4314/jae.v16i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Information Sources on Livelihood of Artisanal Fisherfolk in Inland Fishing Communities in Delta State, Nigeria

Abstract: This study was carried out to examine the effectiveness of information sources on livelihood of artisanal fisherfolk in inland fishing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
1
Order By: Relevance
“…These findings are in consonance with those of Nwabeze et al (2009), who observed that marital status, household size, and educational level were significant and influenced the participation of women in fisheries activities around Nigeria's Kainji Lake Basin. However, the negative relationship with regard to age disagrees with the findings of an earlier study by Nwabeze (2006), which reported that age determines involvement of fishers in livelihood activities in inland fishing communities in Delta State. This discrpancy in results could be attributed to the fact that, irrespective of age, most people assume more roles for higher economic return to meet their household obligations.…”
Section: Effect Of Socioeconomic Variables On Women's Participation Icontrasting
confidence: 83%
See 1 more Smart Citation
“…These findings are in consonance with those of Nwabeze et al (2009), who observed that marital status, household size, and educational level were significant and influenced the participation of women in fisheries activities around Nigeria's Kainji Lake Basin. However, the negative relationship with regard to age disagrees with the findings of an earlier study by Nwabeze (2006), which reported that age determines involvement of fishers in livelihood activities in inland fishing communities in Delta State. This discrpancy in results could be attributed to the fact that, irrespective of age, most people assume more roles for higher economic return to meet their household obligations.…”
Section: Effect Of Socioeconomic Variables On Women's Participation Icontrasting
confidence: 83%
“…The dominance of married households implies that the respondents are likely to be proactive in their fish business because of its immense benefits in ensuring food security, income generation, and reduced vulnerability within the household (Nwabeze, 2006). Most respondents (70%) had a household size of 5-9 people, 18% a household size of 1-4, while 12% had 10-14 persons.…”
Section: Socioeconomic Profile Of the Respondentsmentioning
confidence: 96%
“…Few respondents (8.2%; 1.5%) were into skilled trade and fish farming, respectively (Fig 1). Nwabeze's (2006) study confirmed that fishers engaged in diverse livelihoods activities as coping mechanism and spreading of risk. Table 4 revealed that 71.6% (n=96) of the respondents were engaged in three income generating activities.…”
Section: Analysis Of Fishers' Livelihoods and Adaptive Capacitysupporting
confidence: 66%